2020
DOI: 10.4314/ijbcs.v14i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation des propriétés physico-chimiques et chimiques d'un compost issu d'un mélange de rafles de palmier et de fientes de volaille au Sud-Ouest de la Côte d’Ivoire

Abstract: En Côte d’Ivoire, la pauvreté des sols est une contrainte pour la productivité agricole. L’objectif de cette étude était de produire un compost à base de rafles de palmier afin d’améliorer les propriétés physicochimiques des sols pauvres en matières organiques. Quatre traitements T0 (720 kg de rafles + 0 kg de fientes de volaille), T1 (720 kg de rafles + 200 kg de fientes de volaille), T2 (720 kg de rafles + 400 kg de fientes de volaille) et T3 (720 kg de rafles + 600 kg de fientes de volaille), ont été compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This could be explained by the absence of mineral elements from OPEFB in this medium, which is important for the growth of S. platensis. These results are supported by those obtained by Gnimassoun, Ettien, and Masse (2020) working on the characterisation of the physicochemical properties of compost from a mixture of OPEFB and poultry droppings revealed that OPEFB is very rich in important nutrients for plant growth. On the other hand, the culture medium formulated with 10 g L -1 of OPEFB has a low optical density and biomass, which is explained by the fact that at too high concentrations, the medium becomes rather toxic for the crop.…”
Section: Effect Of Oil Palm Empty Fruit Bunch Medium On Growth Perfor...supporting
confidence: 79%
“…This could be explained by the absence of mineral elements from OPEFB in this medium, which is important for the growth of S. platensis. These results are supported by those obtained by Gnimassoun, Ettien, and Masse (2020) working on the characterisation of the physicochemical properties of compost from a mixture of OPEFB and poultry droppings revealed that OPEFB is very rich in important nutrients for plant growth. On the other hand, the culture medium formulated with 10 g L -1 of OPEFB has a low optical density and biomass, which is explained by the fact that at too high concentrations, the medium becomes rather toxic for the crop.…”
Section: Effect Of Oil Palm Empty Fruit Bunch Medium On Growth Perfor...supporting
confidence: 79%
“…This decrease increases with the amount of manure added in the different treatments, whatever the element, from T0 to T3. The percentage loss was 88.55 to 95.39%, 73.31 to 83% and 81.48 to 87.22% for Cr, Pb and Zn respectively [Gnimassoun et al, 2020]. Indeed, according to Pakou et al (2009), composting reduces the availability of metals present in organic waste.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, high levels of Cr and Zn were observed in the starting materials. This suggests that composting has reduced the metal content of the various composts [Gnimassoun et al, 2020].…”
Section: Resultsmentioning
confidence: 99%
“…Based on Figure 8, T4 recorded the highest value of mean number of fruits per plant while T1, T2 and T3 has the lowest. In a previous study, the use of EFB compost enhanced the yield of soybean by 50% [21]. Furthermore, EFB compost is abundant in nutritional components, which led to the subject of using compost as a fertiliser for the purpose of increasing soil fertility [22].…”
Section: Number Of Fruitmentioning
confidence: 99%